Smuggled Words: Textual Migration and Subversive Assimilation in the Translations of Isaac Bashevis Singer (translation. a transdisciplinary journal, 2022)
A well-known rumor, never confirmed nor dispelled, surrounds the translation of Shakespeare into Yiddish. There is said to have existed a Yiddish translation of King Lear that proclaimed on its title page "fartaytsht un farbesert" ("translated and improved"). Regardless of the rumor's dubious grounding in fact, it stands as both a testament to the stubborn pride with which Yiddish readers and writers viewed their literature (insofar as it could easily not only accommodate but improve upon the great Western classics) and a jibe at the stereotypical insular, unworldly Jew who might believe such a claim (indeed, the assertion that one could "improve" Shakespeare would have been dismissed as a quixotic delusion in most literary traditions).